Internet vigilantism and Ashley Madison : rebranding after a cyberattack - Robson, Karen, (SAGE Knowledge. Cases., 2018)
Avid Life Media was the parent company of a number of dating websites, including Ashley Madison, a dating website for married people seeking affairs. In July 2015, the dating website suffered a massive cyberattack by a group of hackers that resulted in the user data and personal information of nearly 37 million users being publicized. In the aftermath of the attack, Avid Life Media and Ashley Madison have undergone a number of changes in an effort to rebuild and rebrand. This case explores the Ashley Madison brand and the crisis that ensued after the cyberattack. The case encourages students to consider how to approach a complicated business situation involving ethics, customer privacy, cybersecurity, public relations, and rebranding.